Abusive supervision and newcomers' turnover intention: a perceived workplace ostracism perspective. Issue 4 (2nd October 2021) - Wang, Zhenyuan; Du, Jianghong; Yu, Mingyang; Meng, Hui; Wu, Junhong
Abstract: The relationship between abusive supervision and newcomers' turnover intention was explored from the perspective of perceived workplace ostracism. Findings from three-wave data ( n  = 300) showed that (1) abusive supervision was positively associated with newcomers' perceived coworker ostracism, perceived supervisor ostracism, and turnover intention; (2) rather than perceived coworker ostracism, perceived supervisor ostracism was positively associated with newcomers' turnover intention; and (3) the relationship between abusive supervision and newcomers' turnover intention was mediated by perceived supervisor ostracism but not by perceived coworker ostracism. Thus, the hypotheses were partially confirmed. Results underscore the importance of perceived supervisor ostracism in accounting for the relationship between abusive supervision and newcomers' turnover intention. Implications and directions for future research are also discussed.